Public enemies? The differential effects of reputation and celebrity on corporate misconduct scandalization - Han, Jung‐Hoon; Pollock, Timothy G.; Paruchuri, Srikanth (Strategic Management Journal, 2024)
Abstract Research Summary We explore misconduct scandalization's antecedents by focusing on the rational and emotional bases underlying reputation and celebrity, and considering how they can enhance or reduce the likelihood misconduct is scandalized as a function of the misconduct's objective and perceived severity. Specifically, we argue the quantifiable nature of objective misconduct severity enhances reputation's rational influence, but attenuates celebrity's emotion‐based appeal. Conversely, perceived misconduct severity reduces reputation's influence, while enhancing the media‐driven interest in celebrity firms' behaviors. Our findings based on corporate data breaches confirm that objective severity amplifies reputation's effect and attenuates celebrity's effect, while perceived severity amplifies celebrity's effect and attenuates reputation's effect. Our findings highlight the importance of social evaluations' sociocognitive content in understanding why only some misconduct becomes scandalized. Managerial Summary Committing misconduct is costly; having it scandalized is devastating. Yet little is known about how social evaluations influence why only some firms' misconduct is scandalized, beyond the vague notion that prominent firms' misconduct attracts media attention. We find that the rational and emotional bases of firms' evaluations matter. High reputation, based on the rational assessment of firms' capabilities, increases the likelihood of scandalization for objectively severe misconduct, and the influence of celebrity—originating from audiences' emotional resonance with firms' unconventional traits and behaviors—weakens as objective severity increases. Conversely, reputation's influence weakens, and celebrity's influence strengthens, as media “availability cascades” grow and increase perceived severity. In addition to providing a more realistic portrayal of media behavior, we offer insights into post‐misconduct communications and remedial actions.